2017
DOI: 10.1038/s41598-017-10243-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Second Harmonic Generation by Mode Matching in Gain-assisted Double-plasmonic Resonance Nanostructure

Abstract: We theoretically study the gain-assisted double plasmonic resonances to enhance second harmonic generation (SHG) in a centrosymmetric multilayered silver-dielectric-gold-dielectric (SDGD) nanostructure. Introducing gain media into the dielectric layers can not only compensate the dissipation and lead to giant amplification of surface plasmons (SPs), but also excite local quadrupolar plasmon which can boost SHG by mode matching. Specifically, as the quadrupolar mode dominates SHG in our nanostructure, under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Further, this was accompanied by a red shift of the bands. Pan et al 31 theoretically calculated the gain-assisted double plasmonic resonances to enhance second harmonic generation (SHG) in centrosymmetric multilayered nanocomposites. Moreover, PS@ Au synthesized in this study showed ultra-wideband absorption due to coupling between two different layers of the nanogold shell.…”
Section: Resultsmentioning
confidence: 99%
“…Further, this was accompanied by a red shift of the bands. Pan et al 31 theoretically calculated the gain-assisted double plasmonic resonances to enhance second harmonic generation (SHG) in centrosymmetric multilayered nanocomposites. Moreover, PS@ Au synthesized in this study showed ultra-wideband absorption due to coupling between two different layers of the nanogold shell.…”
Section: Resultsmentioning
confidence: 99%
“…Replacing into eqaution (10) the expression of ε 1 given by equation (15), after expanding in powers of y = ε di ε ∞ +ε2 , we obtain,…”
Section: Dispersive Mediummentioning
confidence: 99%
“…Since its proposal in 2003 1 and its first experimental demonstrations in 2009, 2 a wide variety of geometries and materials/metamaterials for the cavities as well as different compounds for the optical-gain medium have been considered. [3][4][5][6][7][8][9][10][11][12][13] Since the first experimental demonstrations in 2009, a wide variety of geometries and materials/metamaterials for the cavities as well as different compounds for the optical-gain medium have been considered 1,[3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the coupling of localized surface plasmons (LSPs) with electromagnetic radiation, a spaser can confine light at subwavelength scales, which can be used to provide a controllable source of on-demand high-intensity electromagnetic fields beyond the diffraction limit. Since its proposal in 2003 [1] and its first, to the best of our knowledge, experimental demonstrations in 2009 [2], a wide variety of geometries and materials/metamaterials for the cavities as well as different compounds for the optical-gain medium have been considered [3][4][5][6][7][8][9][10][11][12][13]. Despite the development of many advanced spasers, most of the research in this area has been focused on natural plasmonic materials such as metals, which have a number of shortcomings, most notably power losses and a fixed charge density that finds applications in the visible and near-infrared range, but not in the mid-infrared and terahertz (THz) region.…”
Section: Introductionmentioning
confidence: 99%